The Role of Investments in the Innovative Development of the Economy - Aminov Fazlitdin Bahodirovich (Research Parks Publishers, 2022)
The article highlights the problems associated with improving the practice of using financial resources in the innovative development of the economy of the Republic of Uzbekistan, and developed scientific proposals for their solution. As well as, the existence of an effective investment and industrial policy of the state (with clear directions for the allocation of financial resources), the development of investment infrastructure, which is the main direction for reducing the risks associated with the implementation of investment projects, the issues of increasing the investment attractiveness of enterprises are analyzed.